2016
DOI: 10.1152/physiolgenomics.00108.2015
|View full text |Cite
|
Sign up to set email alerts
|

Blood transcriptional signature of recombinant human erythropoietin administration and implications for antidoping strategies

Abstract: Recombinant human erythropoietin (rHuEPO) is frequently abused by athletes as a performance-enhancing drug, despite being prohibited by the World Anti-Doping Agency. Although the methods to detect blood doping, including rHuEPO injections, have improved in recent years, they remain imperfect. In a proof-of-principle study, we identified, replicated, and validated the whole blood transcriptional signature of rHuEPO in endurance-trained Caucasian males at sea level (n = 18) and Kenyan endurance runners at modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
3
56
0
1
Order By: Relevance
“…Based on the blood transcriptional signature of recombinant human EPO (rHuEPO), Salamin et al demonstrated that delta‐aminolevulinate synthase 2 ( ALAS2 ), carbonic anhydrase ( CA1 ), and solute carrier family 4 member 1 ( SLC4A1 ) were down‐regulated after reinfusion of donated blood . Using a different method of quantitation (RT‐qPCR), we confirmed the results of this pilot study with additional subjects ( n = 15 vs 7) and time points tested ( t = 8 vs 5) (Figure A).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Based on the blood transcriptional signature of recombinant human EPO (rHuEPO), Salamin et al demonstrated that delta‐aminolevulinate synthase 2 ( ALAS2 ), carbonic anhydrase ( CA1 ), and solute carrier family 4 member 1 ( SLC4A1 ) were down‐regulated after reinfusion of donated blood . Using a different method of quantitation (RT‐qPCR), we confirmed the results of this pilot study with additional subjects ( n = 15 vs 7) and time points tested ( t = 8 vs 5) (Figure A).…”
Section: Resultsmentioning
confidence: 82%
“…It suggests that transcriptomic biomarkers might be promising complements to hematological parameters of the ABP in a longitudinal monitoring for the detection of transfusion. Moreover, as demonstrated by Durussel et al, these genes might also serve as biomarkers of rHuEPO administration …”
Section: Resultsmentioning
confidence: 99%
“…An alternative strategy for identifying EPO misuse in doping controls was presented by Durussel et al ., who investigated the effect of EPO injections on the whole blood transcriptional signature . A drug intervention study was conducted with 18 Caucasian and 18 African trained volunteers, who received 50 IU/kg every two days over a period of 4 weeks.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Previously, Salamin et al suggested that measurements of gene transcripts from reticulocytes in RNA stabilized blood tubes could be biomarkers of blood transfusion . It was also demonstrated that the same strategy was applicable for the detection of erythropoietin stimulating agents in micro‐doses . RNA stabilized blood tubes such as Tempus™ blood RNA tubes are mainly used for multi‐site clinical studies in order to facilitate the transport and storage of samples .…”
Section: Introductionmentioning
confidence: 99%